THE INFLUENCE OF PERSONAL HYGIENE AND THE USE OF DRINKING WATER ON DIARRHEA PREVENTION EFFORT IN CHILDREN IN SOROPIA HEALTH CENTRE, KONAWE REGENCY: PERSONAL HYGIENE - Riyani Kartika Puspa Sari; Timbul Supodo; Sunarsih Sunarsih (STIKes Mandala Waluya Kendari, 2022)
Background: The preliminary survey in Soropia Health Center on 10 (ten) mothers who had toddlers, there were 8 (eight) people (80%) lacking personal hygiene and 2 (two) people (20%) having sufficient personal hygiene, and then 6 (six) people ( 60%) environmental sanitation is sufficient and 4 (four) people (40%) were lacking. In terms of food processing, there were 7 (seven) people (70) food processing in the poor category and 3 (three) people (30%) food management is adequate , then 4 (four) people (40%) who used drinking water in the less category and 6 (six) people (60%) used drinking water in the sufficient category, the survey also show that the knowledge of mothers who had toddlers was mostly 7 ( seven) people (70%) in the poor category and 3 (three) people (30%) in the sufficient category. Methods: This type of research is quantitative with Quasy experimental design. The population in this study were all toddlers aged 0-59 months who experienced diarrhea in the work area of the Soropia Health Center, Konawe Regency in 2020 as many as 79 people. The sample size is 66 respondents which are divided into two, namely 33 respondents in the intervention group and 33 in the control group. The sampling technique of treatment and control used simple random sampling and control. Result: This researchfound a p value of 0.000 < 0.05 for personal hygiene, and the use of drinking water. Conclusion: There is an effect of personal hygiene and use of drinking water on efforts to prevent diarrhea in children under five in Soropia Health Center, Konawe Regency.